Pharmacophore methods in drug discovery - Van Drie, John H. (Henry Stewart Talks, 2021)
The roles of pharmacophores in drug discovery, Definition of pharmacophore, calculating pharmacophore from a structure-activity relationship, Pharmacophores-based virtual screening, Lead optimization, Computational approach for drug discovery project